Effect of Dexmedetomidine Nebulization on the Hemodynamic Parameters during Laryngoscopy and Endotracheal Intubation (Nepal Medical College Journal, 2025)
Dexmedetomidine is an alpha-2 agonist used to attenuate the hemodynamic response to laryngoscopy and endotracheal intubation via the intravenous route. Our study was performed in 390 patients undergoing general anesthesia to assess the effect of dexmedetomidine nebulization on the hemodynamic parameters during laryngoscopy and endotracheal intubation. Group D received 0.75 mcg/kg dexmedetomidine diluted in 0.9% normal saline and group S received 3 ml of normal saline 30 minutes before induction of anesthesia. After laryngoscopy and intubation there was significantly lower trend of increase in heart rate and systolic blood pressure in group D (p